Climate-Smart Agriculture: What is it? Why is it needed? - CGIAR Research Program on Climate Change, Agriculture and Food Security; Food and Agriculture Organization of the United Nations (Food and Agriculture Organization of the United Nations, 2014)
In the next 20 years, increasing the productivity and incomes from smallholder crop, livestock, fishery and forestry production systems will be key to achieving global food security. Most of the world’s poor are directly or indirectly dependent on agriculture, and experience has shown that growth in agriculture is often the most effective and equitable strategy for reducing poverty and increasing food security. Climate change multiplies the challenges of achieving the needed growth and improvements in agricultural systems, and its effects are already being felt. Climate-Smart Agriculture (CSA) is an approach to dealing with these interlinked challenges in a holistic and effective manner. This brief is intended to give an overview of the approach and its main features, as well as answers to frequently asked questions about it.